Assessing five decades of change in a high Arctic parasitoid community. Issue 11 (25th January 2013) - Timms, Laura L.; Bennett, Andrew M. R.; Buddle, Christopher M.; Wheeler, Terry A.
Abstract : Arctic ecosystems are fragile, and are particularly sensitive to the pressures of climate change. Both average temperature and precipitation have increased over the past five decades on Ellesmere Island, Nunavut, Canada in the high Arctic. Altered growth forms and increased biomass in dominant plant species on Ellesmere Island have been observed concurrent with the changing climate, but shifts in the diversity or rank abundance of plant and bird species have not been detected. Changes in diversity may take longer to appear, or may be assessed better using organisms with shorter generation times such as insects. We explored the ecological impacts of climate change on Ellesmere Island using historical and contemporary communities of ichneumonid wasps. We compared community diversity, functional composition, and body size of two common species using ichneumonid specimens collected in 1961–1965, 1980–1982, 1989–1992, and 2010. We found high compositional similarity between collections, overlapping estimates of species richness, no change in the proportion of idiobiont genera in the community, and no clear pattern in body size over time. The greatest amount of variation over time was detected in parasitoids of herbivores; proportionally fewer herbivore‐parasitizing genera were found in 2010 than in historical collections, and the two genera that were only found in one of the four collections were both parasitoids of herbivores. Our results point to the need to assess climate change effects in Arctic systems using a range of taxa, and responses to large‐scale environmental disturbances may be idiosyncratic and difficult to predict.